Consensus guidelines on the use of bisphosphonate therapy in children and adolescents. (5th March 2018) - Simm, Peter J; Biggin, Andrew; Zacharin, Margaret R; Rodda, Christine P; Tham, Elaine; Siafarikas, Aris; Jefferies, Craig; Hofman, Paul L; Jensen, Diane E; Woodhead, Helen; Brown, Justin; Wheeler, Benjamin J; et al.
Abstract: Bisphosphonate therapy is the mainstay of pharmacological intervention in young people with skeletal fragility. The evidence of its use in a variety of conditions remains limited despite over three decades of clinical experience. On behalf of the Australasian Paediatric Endocrine Group, this evidence‐based consensus guideline presents recommendations and discusses the graded evidence (using the GRADE system) for these recommendations. Primary bone fragility disorders such as osteogenesis imperfecta are considered separately from osteoporosis secondary to other clinical conditions (such as cerebral palsy, Duchenne muscular dystrophy). The use of bisphosphonates in non‐fragility conditions, such as fibrous dysplasia, avascular necrosis, bone cysts and hypercalcaemia, is also discussed. While these guidelines provide an evidence‐based approach where possible, further research is required in all clinical applications in order to strengthen the recommendations made.